Biomass yield, oil productivity and fatty acid profile of Chlorella lobophora cultivated in diverse eutrophic wastewaters. (July 2017) - Santhosh Kumar, K.; Prasanthkumar, S.; Ray, J.G.
Abstract: Experimental trial of biomass yield, oil productivity and fatty acid profile of Chlorella lobophora in natural eutrophic wastewaters from three different sources was carried out using Bold's Basal Medium as the control. Eutrophication of water is a serious environment issue in agricultural as well as in many industrial zones in the world. But algal biomass production remains the most cost-effective and sustainable means to deal with eutrophic wastewater. Algal culture is the potential method of combining wastewater treatment, nutrient removal, resource recovery and simultaneous yield of biomass and bio-oils. Algal biomass has nutraceutical and biofuel applications. The major objective of the present experimentation was to test the suitability of different eutrophic wastewaters towards understanding the optimum requirements of microalgae for best biomass and oil yield. Influence of variations in nutrient composition of the wastewaters on chemical profile of the oil are also analyzed. Different water quality parameters were found significantly correlated to biomass characteristics of the alga. Oil productivity as well as chemical profile of the oil also exhibited interrelationships to water quality parameters. The oil of algal biomass taken from all kinds of wastewater sources is found suitable for biodiesel through transesterification. Overall, the method stands as model for preliminary screening of algae for economic utilization of wastewaters towards attaining high biomass yield with desired oil quality, especially for biodiesel production. Graphical abstract: Highlights: Biomass yield and oil productivity of Chlorella lobophora in eutrophic waters against BBM medium. Assessment of the suitability of different eutrophic waters towards optimum biomass and oil yield. Correlation between nutrients and fatty acid profile in Chlorella lobophora .